Case of pulmonary sarcoidosis relapsed as unilateral carpal tunnel syndrome: Arare case report - Singh, Ashok Kumar; Tiwari, Ajeet; Nigam, Saket; Gupta, Deepti (Indian Journal of Case Reports, 2025)
Sarcoidosis is a multisystemic chronic inflammatory disease with variable clinical manifestations and having a tendency to relapse of the disease in the same organ and other organs as well. Extrapulmonary relapse is rarely reported in the literature. Here, we are reporting the case of a 56-year-old female with a known case of pulmonary sarcoidosis for 21 years, which was asymptomatic since then, now presented as unilateral carpal tunnel syndrome secondary to extrapulmonary sarcoidosis relapse. Diagnosis was confirmed by open biopsy, which revealed noncaseating granulomas in resected tissue. She was treated successfully by surgical intervention and systemic steroids.